Educative Non-privative Measures of Freedom - ZAU, Raul Teodor (Journal of Legal Studies, 2017)
Infractionality or criminality in minor rank, even if it is a component of a general infractional phenomenon, it shows some particularities determined by biological, psychological and social characteristics of minor persons which Romanian legislature had in mind when it had foreseen their criminal liability. For this, The New riminal Code, stipulates some regulations on the educational measures regarding non privacy of freedom - three conditions from the file - Recommandations R nr. 16/1992 of the European Committee. Measures regarding the non privacy of freedom are sanctions applied by the court and the young defendant is still in the society with some obligations on his side or institution which was bound by the court in the name of the law. The issue of this measure is to educate and reeducate the minor person who commited a crime, to ensure a change in his conscience to respect social values.